RTA: Menumbuhkan Kesadaran Manusia Taat Hukum Brahman (Absolut Transcendental) - I Nengah Juliawan; Putu Ersa Rahayu Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The law is a kind of nature of God's power that is shown in a form that can be seen and experienced by every living being without exception. This pure and eternal form of God's law, in Hinduism is called the Rta. The Law of Apostates is a pure law that is absolute transcendental with its legal form called Dharma. Rta in Hinduism became the basis of karmaphala teachings. It is this rta that regulates the consequences of human behavior as a unity invisible to man and the universe is controlled by the laws of birth (Utpeti), life (Stiti) and death (Pralina), and no one can avoid the law. If this Rta is violated or not obeyed according to its rules then there will be disharmony in this life, disasters will occur everywhere, and destruction will come again and again. people who follow the law taught by sacred libraries and follow sacred customs gain notoriety in this world and after death receive infinite happiness.Keywords: Rta, Law, Brahman, Consciousness